Investigating the Impact of Ownership Structure and Board Characteristics on Accounting Conservatism in Financial Reports of Iraq and UAE - Owaid AL- Zubaidi, Waleed Mohsin; Saedi, Rahman; Abed Mousa Alsabary , Ibrahim; Rahimi Dastjerdi , Mohsen (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study examines the impact of corporate governance mechanisms on accounting conservatism in companies listed on the Iraq and UAE stock exchanges. Methods and Materials: The statistical sample of the study was selected systematically from companies listed on the Iraq and UAE stock exchanges during the period from 2016 to 2022. This sample includes 31 companies from the Baghdad Stock Exchange and 52 companies from the Abu Dhabi and Dubai stock exchanges. Additionally, the hypotheses of the study were tested using the panel data regression method. Findings: The results of hypothesis testing indicated that the board size, board independence, managerial ownership, and institutional ownership have a positive and significant impact on accounting conservatism in companies listed on the UAE stock exchange. Moreover, the results showed that only board size has a negative and significant relationship with conservatism in the Iraq stock exchange, while the other results were similar to those of the UAE stock exchange. Conclusion: The study concludes that board characteristics and ownership structure significantly influence accounting conservatism in Iraq and UAE, with notable differences observed in board size’s impact across the two markets.